2018
DOI: 10.1007/s10142-018-0641-9
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of microarray expression profiles of circRNAs and lncRNAs with associated co-expression networks in human colorectal cancer

Abstract: Increasing data demonstrate that circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs) play important roles in tumorigenesis. However, the mechanisms in colorectal cancer (CRC) remain unclear. Here, hundreds of significantly expressed circRNAs, and thousands of lncRNAs as well as mRNAs were identified. By qRT-PCR, one abnormal circRNA, lncRNA, and three mRNAs were verified in 24 pairs of tissues and blood samples, respectively. Then, by GO analysis, we found that the gene expression profile of linear cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…This phenomenon seems to be independent of the expression tendencies of single circRNAs and linear transcripts, while the aforementioned ratio and the cell proliferation index are inversely associated [ 42 ]. The same tendency has also been observed in other research studies [ 43 , 44 ]. Interestingly, following the comparison of circRNA expression profiles among CRC cell lines with distinct KRAS mutational status, Dou et al demonstrated that circRNA expression levels in KRAS -mutated cells are significantly lower than in the KRAS -wild type cells, while they showed that circRNAs can be transferred to exosomes, where they are abundant [ 45 ].…”
Section: Expression Of Circrnas In Crcsupporting
confidence: 90%
“…This phenomenon seems to be independent of the expression tendencies of single circRNAs and linear transcripts, while the aforementioned ratio and the cell proliferation index are inversely associated [ 42 ]. The same tendency has also been observed in other research studies [ 43 , 44 ]. Interestingly, following the comparison of circRNA expression profiles among CRC cell lines with distinct KRAS mutational status, Dou et al demonstrated that circRNA expression levels in KRAS -mutated cells are significantly lower than in the KRAS -wild type cells, while they showed that circRNAs can be transferred to exosomes, where they are abundant [ 45 ].…”
Section: Expression Of Circrnas In Crcsupporting
confidence: 90%
“…They could competitively bind to the miRNA and then decrease the inhibitory effect of the miRNA on the expression of target genes 23, 24. Many studies have proved that circRNAs are potential biomarkers and participate in pathogenesis of various autoimmune diseases 25, 26, 27. For instance, decreased hsa_circ_0044235 in PBMCs has been confirmed to have significant value in the diagnosis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Newly generated researches showed that noncoding RNAs displayed importance in carcinogenesis and cancer development [ 51 ]. Some reports have shown that circRNAs displayed importance in the process of biology and the progression of diseases through sponging miRNA [ 13 , 14 ]. For example, circular RNA Circ100084, exhibiting as the sponge of miR-23a-5p, modulated the expression of IGF2 in hepatocarcinoma [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some researches had shown that circRNAs modulated alternative splicing and gene expression level through sponging microRNAs (miRNAs) [ 11 , 12 ]. At the same time, disorders of circRNAs took part in carcinogenesis and cancer development of CRC [ 13 , 14 ], liver cancer [ 15 ], and gastric cancer [ 16 – 19 ]. These findings indicated that circRNAs, as a new kind of endogenous noncoding RNA, have been a new hotspot in the cancer research and probably would exhibit important functions in the development of tumor.…”
Section: Introductionmentioning
confidence: 99%